The relationship between emotional regulation and depression among adolescent in Bangladesh - Tanni, K. T.; Zainudin, Zaida Nor; Hassan, Siti Aishah; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2021)
Depression is a major public health issue both in Bangladesh and in the world and should be given more focus, in particular to the identification of prevention and intervention targets. The research aimed at researching relationships between the strategy of emotional regulation and adolescent depression. This quantitative study chose the youth population in Dhaka City, Bangladesh. The researcher selected the participants randomly from among those in the 7th to 10th grades. A class with 40 participants was selected. The researcher sent questionnaires to the participants and obtained their responses to the questionnaires. The data from this study were used to examine the relationship between emotional control and depression in adolescents in Bangladesh by using the Spearman correlation analysis. The findings show that the relationships between emotional regulation and depression, higher extents of ‘suppression-focused’ emotional regulation styles appear to be related to the reporting of more borderline clinical depression, while more cognitive ‘reappraisal-focused’ styles are not significantly associated with the symptoms of depression. The outcomes concerning the connections between cognitive strategies for emotional regulation and depression may serve as potential targets for a mental health intervention for adolescents in developing countries. This study outcome will also contribute to the adolescent crisis intervention strategy among adolescent in Bangladesh. In the individual and group treatment sessions, the therapists may use a strategy plan for adaptive emotional regulations to prevent depression.